Medication Adherence Among Hypertensive Patients in Kurdistan Region of Iraq: An Observational Follow-Up Study - Deldar Morad Abdulah; Saeid Khezer Ahmed; Zuhair Rushdi Mustafa (National Journal of Community Medicine, 2024)
Background: Adherence to medications is a main concern to hypertension control and incidence of CVD complications. This study aimed to measure the level of medication adherence of hypertensive patients after one month follow-up.